Evaluation of the drug management system at the pharmaceutical supplies installation of the Tegal City Health service in 2019 - Wibawa, Anggun Setya; Widodo, Gunawan Pamudji; Iswandi, Iswandi (Science Midwifery, 2025)
Drug management involves a series of interconnected activities, including planning, procurement, receipt, storage, distribution, control, recording, reporting, disposal, monitoring, and evaluation. This study aimed to evaluate the drug management system, identify challenges and solutions, and assess its compliance with the 2010 Ministry of Health standards at the Pharmaceutical Supply Installation of the Tegal City Health Office. A descriptive design was used, with retrospective data collected from 2019 documents. Primary data were obtained through direct observation and in-depth interviews to identify obstacles, while secondary data were sourced from drug management records based on ten indicators and compared with the 2010 standards. The results revealed several discrepancies: in the planning stage, drug conformity with the Fornas Level I reached 92.54% and planning accuracy was 184.22%; in procurement, drug availability was 92.04%, generic drugs 88.97%, and budget allocation 98.14%. Storage met standards, with 0% expired or damaged drugs. In distribution, the proportion of drugs in the safe category was 46.27% and average stock-out duration was 27.40%, while distribution accuracy reached 100%. Key challenges include the presence of non-Fornas drugs, disruptions in the e-logistics reporting system, and procurement delays due to an underdeveloped e-catalogue system. Recommended solutions include regular training for drug management staff, improved coordination with the TPOT team based on clinical and pharmacoeconomic considerations, and the addition of pharmacist personnel.